Partage des rôles dans les couples à deux revenus et satisfaction de l’équilibre travail-famille selon le genre - Boulet, Maude; Le Bourdais, Céline (Cahiers de recherche sociologique, 2017)
La hausse de la participation des femmes au marché du travail a contribué au recul du modèle familial traditionnel de l’homme pourvoyeur et de la femme au foyer. Conséquemment, les relations entre les sexes ont été bouleversées; un bouleversement que certains auteurs qualifient de révolution des rôles de genre. C’est dans cette perspective des rôles de genre que le présent article examine l’effet du partage des tâches domestiques et de l’articulation du temps travaillé au sein des couples à deux revenus au Québec et dans le reste du Canada sur la satisfaction de l’équilibre travail-famille. Basée sur une exploitation de l’Enquête sociale générale de 2011, l’analyse révèle une association positive entre division traditionnelle des tâches domestiques et satisfaction parmi les Québécoises et entre partage traditionnel du temps travaillé et satisfaction parmi les femmes vivant ailleurs au Canada. De leur côté, les hommes qui assument la plus grande part des tâches domestiques paraissent moins satisfaits de l’équilibre travail-famille que ceux qui partagent également ces tâches avec leur conjointe. Enfin, le fait de travailler de longues heures, soit plus de 40 heures/semaine, a un impact négatif sur la satisfaction des hommes et des femmes, quel que soit leur lieu de résidence.
Keywords: 2000 à aujourd'hui; 2010-2019; amérique du nord; amériques; approches et analyses; canada; care; couple; cours; discipline; hétérosexualité; inégalités; maternité; premier cycle; périodes historiques; québec; rapports sociaux de sexe; relations amoureuses; régions géographiques; sciences humaines; sexualité; soc2264; sociologie; systèmes d'oppressions; thématiques; travail

Gender: Psychological perspectives - Brannon, Linda (Routledge, 2017)
"Gender: Psychological Perspectives" synthesizes the latest research on gender to help students think critically about the differences between research findings and stereotypes, provoking them to examine and revise their own preconceptions. The text examines the behavioral, biological, and social contexts in which women and men express gendered behaviors. The text's unique pedagogical program helps students understand the portrayal of gender in the media and the application of gender research in the real world. – From publisher's description. Contenu : Preface – Acknowledgements – About the author – The study of gender – Researching sex and gender – Gender stereotypes: masculinity and femininity – Hormones and chromosomes – Theories of gender development – Developing gender identity – Intelligence and cognitive abilities – Emotion – Relationships – Sexuality – School – Careers and work – Health and fitness – Stress, coping, and psychopathology – Treatment for mental disorders – How different? – References – Index.
Section: xix, 539 pages ; 26 cm
Keywords: approches et analyses; biologie; comportements sexuels; cours; différence des sexes; discipline; discours dominant; identité sexuelle; maternité; paternité; premier cycle; psy4910; psychologie; relations amoureuses; santé; santé mentale; sciences; sciences humaines; sexisme; sexualité; stéréotypes de genre; systèmes d'oppressions; thématiques; violences; violences sexuelles; études de genres

Negotiating Parental designations among trans parents' families: An ecological model of Parental identity - Petit M.-P.; Julien D.; Chamberland L. (Psychology of Sexual Orientation and Gender Diversity, 2017)
Parental designations contribute to construct parental identity in the eyes of the child, the parent, and the generalized others. In a hetero/cisnormative context that offers only 2 options for parental identity (male fathers and female mothers), this study (a) provided an overview of the parental designations of trans people and their evolution as parents transitioned, (b) and generated a model of factors associated with the choice of posttransition parental designations. Semistructured interviews guided by the Bronfenbrenner’s ecological model (1988) were administered to 24 Canadian trans parents. The content of the interviews was analyzed using thematic analyses. Results showed that the choice of parental designations was influenced by the timing of childbirth, parents’ consideration of normative strains, negotiation with their children, and issues related to public spaces. Overall, trans parental identity appeared as a multidimensional, multidetermined, nonbinary, and fluid identity in a context of nonalignment between the sex assigned at birth and gender identity. Institutional forms and legislation relative to parenting and birthing must acknowledge the diversity of parental identity and designations.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; famille; identités LGBTQIA2+; maternité; parentalité; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; soc2264; sociologie; thématiques; transféminisme

Radical reproductive justice: Foundation, theory, practice - Ross, Loretta; Roberts, Lynn; Derkas, Erika; Peoples, Whitney; Bridgewater Toure, Pamela (Feminist press, 2017)
Expanding the social justice discourse surrounding "reproductive rights" to include issues of environmental justice, incarceration, poverty, disability, and more, this crucial anthology explores the practical applications for activist thought migrating from the community into the academy. Radical Reproductive Justice assembles two decades’ of work initiated by SisterSong Women of Color Health Collective, creators of the human rights-based “reproductive justice” framework to move beyond polarized pro-choice/pro-life debates. Rooted in Black feminism and built on intersecting identities, this revolutionary framework asserts a woman's right to have children, to not have children, and to parent and provide for the children they have.
Keywords: afro-féminisme; approches et analyses; discipline; droit; droits des femmes*; intersectionnalité; justice reproductive; justice sociale; maternité; militance; santé; science politique et droit; sciences humaines; sociologie; thématiques